Treatment of industrial effluents in constructed wetlands: Challenges, operational strategies and overall performance. (June 2015) - Wu, Shubiao; Wallace, Scott; Brix, Hans; Kuschk, Peter; Kirui, Wesley Kipkemoi; Masi, Fabio; Dong, Renjie
Abstract: The application of constructed wetlands (CWs) has significantly expanded to treatment of various industrial effluents, but knowledge in this field is still insufficiently summarized. This review is accordingly necessary to better understand this state-of-the-art technology for further design development and new ideas. Full-scale cases of CWs for treating various industrial effluents are summarized, and challenges including high organic loading, salinity, extreme pH, and low biodegradability and color are evaluated. Even horizontal flow CWs are widely used because of their passive operation, tolerance to high organic loading, and decolorization capacity, free water surface flow CWs are effective for treating oil field/refinery and milking parlor/cheese making wastewater for settlement of total suspended solids, oil, and grease. Proper pretreatment, inflow dilutions through re-circulated effluent, pH adjustment, plant selection and intensifications in the wetland bed, such as aeration and bioaugmentation, are recommended according to the specific characteristics of industrial effluents. Graphical abstract: Highlights: Knowledge on use of wetlands treating various industrial effluents is insufficient. Updated concept and functional mechanisms in wetlands were summarized. Benefits and limitations of wetlands treating industrial effluents were evaluated. Effluent recirculation and intensifications in the wetlands are recommended. Abstract : A comprehensive knowledge on application of CWs for treatment of various industrial effluents is reviewed in aspects of challenges, operational strategies and overall performance.